Chemical-Exchange and Paramagnetic T2Relaxation Agents for Water Suppression in Spin-Echo Proton Nuclear Magnetic Resonance Spectroscopy of Biological Fluids - Connor,S; Nicholson,JK; Everett,JR (Analytical Chemistry, 1987)
The WATR (water attenuation by T2relaxation) method was used to effect solvent suppression In 400-MHz spin-echo 1H NMR spectra of urine, blood plasma, bile, and seminal plasma. Both chemical-exchange (urea and guanidinium salts) and paramagnetic relaxation agents (Mn2+ and Gd3+ ions) were effective in attenuating the water signal in spin-echo spectra of urine. However, the paramagnetic ions form coordination complexes with many blofluld metabolites (e.g. citrate, lactate, and hippurate) so attenuating their proton resonances. The concentrations of these metabolites In bioflulds are sufficient to modulate the relaxation effects of the paramagnetic ions on the water protons, hence reducing the efficiency of the WATR method. Indeed, Mn2+ ions were ineffective at reducing the water T2’s in blood and seminal plasmas, unless used in amounts that significantly attenuated metabolite resonances. By contrast urea and guanidinium salts were very effective as water relaxation agents in all bioflulds studied. New resonance assignments for bile and seminal plasma are reported. © 1987, American Chemical Society. All rights reserved.